2017
DOI: 10.1080/21645515.2016.1271518
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of measles in refugees arriving at Los Angeles International Airport from Malaysia

Abstract: BackgroundOn August 24, 2011, 31 US-bound refugees from Kuala Lumpur, Malaysia (KL) arrived in Los Angeles. One of them was diagnosed with measles post-arrival. He exposed others during a flight, and persons in the community while disembarking and seeking medical care. As a result, 9 cases of measles were identified.MethodsWe estimated costs of response to this outbreak and conducted a comparative cost analysis examining what might have happened had all US-bound refugees been vaccinated before leaving Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Two studies published after the economic analysis systematic review was performed examined different costs associated with pre-departure vaccinations, one in the context of a response to an outbreak [ 55 ] and the second evaluating the US Vaccination Program for US-bound Refugees (VPR) [ 56 ]. The first study showed that pre-departure vaccination of all US bound refugees would not only improve health, reduce importations of VPD, but be cost saving when considering all the resources required for response to outbreak activities.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies published after the economic analysis systematic review was performed examined different costs associated with pre-departure vaccinations, one in the context of a response to an outbreak [ 55 ] and the second evaluating the US Vaccination Program for US-bound Refugees (VPR) [ 56 ]. The first study showed that pre-departure vaccination of all US bound refugees would not only improve health, reduce importations of VPD, but be cost saving when considering all the resources required for response to outbreak activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous outbreaks were confined to either transmission of measles at airports or at hospitals. 5,6,9,10 In nonendemic areas, air travel was considered as a risk factor for the introduction of measles in a highly vaccinated population. 19 The measles seropositive rates among all age groups from 2011 to 2017 in Hong Kong were >95%, 2 exceeding the cutoff of 93%-95% required to prevent sustained local transmission.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, international travel facilitates intercontinental measles transmission, 3 which can affect the small number of unimmunized persons and those with primary or secondary vaccine failure. 4 Outbreaks of measles have been reported in international airports in the United Kingdom, The Netherlands, 5 the United States, [6][7][8] and Japan. 9 Nosocomial outbreaks of measles in emergency departments, triage wards, and waiting rooms of the hospitals have also been summarized.…”
mentioning
confidence: 99%
“…For example, international and domestic costs for just one of these outbreaks were estimated at $130,000, partly due to the high costs of travel cancellations and rebookings. 20 …”
Section: Beyond the Technical Instructions: The Refugee Health Initiamentioning
confidence: 99%